Peran Rhizopus Spp. dalam Tempe sebagai Agen Antimikroba Alami: Studi Praktikum Farmasi Berbasis Eksperimen - Latifatus Zahroh; Ardi Mustakim (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Tempe is a traditional Indonesian fermented product that is rich in nutrients, easily digestible, and functions as a functional food. Fermentation by Rhizopus spp., particularly R. oligosporus, produces bioactive compounds with potential antimicrobial activity. This study aimed to demonstrate the antimicrobial activity of tempe extract against Staphylococcus aureus, Escherichia coli, and Candida albicans using the disc diffusion and broth dilution methods. Tempe extract fermented for 48–72 hours showed inhibition zones of 24–26 mm, 17–19 mm, and 20–23 mm, respectively. Microscopic analysis confirmed the characteristic features of Rhizopus spp., while TLC and HPLC assays identified phenolic compounds and isoflavones as active components. These findings highlight that Rhizopus spp. not only plays a role in fermentation but also produces secondary metabolites with antibacterial and antifungal activity, suggesting that tempe has potential to be developed as a natural source of bioactive compounds in pharmacy and alternative medicine.